Transcellular blood-brain barrier disruption in malaria-induced reversible brain edema - Jin, Jessica; Ba, Mame Aida; Wai, Chi Ho; Mohanty, Sanjib; Sahu, Praveen K.; Pattnaik, Rajyabardhan; Pirpamer, Lukas; Fischer, Manuel; Heiland, Sabine; Lanzer, Michael; Frischknecht, Friedrich; Müller, Ann-Kristin; et al. (Life science alliance, 2022)
Brain swelling occurs in cerebral malaria (CM) and may either reverse or result in fatal outcome. It is currently unknown how brain swelling in CM reverses, as brain swelling at the acute stage is difficult to study in humans and animal models with reliable induction of reversible edema are not known. In this study, we show that reversible brain swelling in experimental murine CM can be induced reliably after single vaccination with radiation-attenuated sporozoites as proven by in vivo high-field magnetic resonance imaging. Our results provide evidence that brain swelling results from transcellular blood-brain barrier disruption (BBBD), as revealed by electron microscopy. This mechanism enables reversal of brain swelling but does not prevent persistent focal brain damage, evidenced by microhemorrhages, in areas of most severe BBBD. In adult CM patients magnetic resonance imaging demonstrate microhemorrhages in more than one third of patients with reversible edema, emphasizing similarities of the experimental model and human disease. Our data suggest that targeting transcellular BBBD may represent a promising adjunct therapeutic approach to reduce edema and may improve neurological outcome.